2012
DOI: 10.1371/journal.pone.0043951
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Lower Female Genital Tract Soluble and Cellular Biomarkers: Defining Levels and Predictors in a Cohort of Healthy Caucasian Women

Abstract: BackgroundHigh concentrations of pro-inflammatory cytokines have been previously observed in the genital fluids of women enrolled in microbicide trials and may explain observed increased HIV transmission in some of these trials. Although the longitudinal nature of these studies allows within-subject comparisons of post-product levels to baseline levels, the fact that the physiologic variations of these cytokines and other markers of immune activation are not fully defined in different populations, makes it dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 58 publications
7
71
1
Order By: Relevance
“…45 No significant differences in the antimicrobial activity of the CVL The secretion of cervical mucus is significantly influenced by endogenous reproductive hormones, with cervical mucus volume peaking with surges in preovulatory serum E2. [46][47][48] The biologic rationale for differences in antimicrobial activity of the CVL is based on data from small cohorts showing that secreted cytokines, chemokines, and other cationic antimicrobial polypeptides in the vagina have significant alterations in concentrations based on the phase of the menstrual cycle with immune factors such as IL-6, IL-1b, IL-1RA, and MIP-1b being significantly higher in the FOL phase versus the LUT phase, 19,27 while IL-1a and b-defensin were significantly elevated in the LUT phase. 27 Keller et al found that immune mediators, SLPI, a and b defensins, lysozyme, and lactoferrin, were significantly lower at mid-cycle ovulation compared with both the FOL and LUT phases.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 99%
See 3 more Smart Citations
“…45 No significant differences in the antimicrobial activity of the CVL The secretion of cervical mucus is significantly influenced by endogenous reproductive hormones, with cervical mucus volume peaking with surges in preovulatory serum E2. [46][47][48] The biologic rationale for differences in antimicrobial activity of the CVL is based on data from small cohorts showing that secreted cytokines, chemokines, and other cationic antimicrobial polypeptides in the vagina have significant alterations in concentrations based on the phase of the menstrual cycle with immune factors such as IL-6, IL-1b, IL-1RA, and MIP-1b being significantly higher in the FOL phase versus the LUT phase, 19,27 while IL-1a and b-defensin were significantly elevated in the LUT phase. 27 Keller et al found that immune mediators, SLPI, a and b defensins, lysozyme, and lactoferrin, were significantly lower at mid-cycle ovulation compared with both the FOL and LUT phases.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 99%
“…[46][47][48] The biologic rationale for differences in antimicrobial activity of the CVL is based on data from small cohorts showing that secreted cytokines, chemokines, and other cationic antimicrobial polypeptides in the vagina have significant alterations in concentrations based on the phase of the menstrual cycle with immune factors such as IL-6, IL-1b, IL-1RA, and MIP-1b being significantly higher in the FOL phase versus the LUT phase, 19,27 while IL-1a and b-defensin were significantly elevated in the LUT phase. 27 Keller et al found that immune mediators, SLPI, a and b defensins, lysozyme, and lactoferrin, were significantly lower at mid-cycle ovulation compared with both the FOL and LUT phases. 20 Secretion of mannosebinding lectin, a molecule in the complement system that plays a critical role in host protection, from vaginal epithelial cells is increased in the LUT phase of the menstrual cycle.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 99%
See 2 more Smart Citations
“…CVL samples and vaginal swabs were shipped in batches using a temperature-monitored dry shipper to the central laboratory at the Institute of Tropical Medicine (ITM) in Antwerp, Belgium, where they were stored at Ϫ80°C before analysis for soluble markers of inflammation or use in the CVL antiviral assay. The concentrations of the cytokines interleukin-1␣ (IL-1␣), IL-1␤, IL-6, and IL-12(p70), the CC chemokine MIP-1␤, the CXC chemokines gamma interferon (IFN-␥)-induced protein (IP-10) and IL-8, and the growth factors granulocyte-macrophage colony-stimulating factor (GM-CSF) and granulocyte colony-stimulating factor (G-CSF) in CVL samples were analyzed at the ITM in Antwerp, Belgium, using the Bio-Plex human cytokine assay kit (Bio-Rad Laboratories NV-SA, Nazareth, Belgium) as previously described (11). Fluorescence data for nine soluble immune mediators were collected using a Bio-Plex array reader, and Bio-Plex Manager 5.0 software was used to calculate cytokine concentrations with a weighted five-parameter logistic curve-fitting method on the 4-fold dilution series of the standard provided with the kit at the ITM.…”
Section: Study Participantsmentioning
confidence: 99%